RELATIONSHIP BETWEEN HUMAN RESOURCE MANAGEMENT AND TEACHER EFFECTIVENESS IN SOME SELECTED SECONDARY SCHOOLS IN CROSS RIVER STATE, NIGERIA. - Mera, Muhammad Satatu (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2023)
The paper examined the relationship between human resource management and teacher effectiveness in some selected secondary schools in cross rivers state, Nigeria. Five research questions and five research hypotheses guided the study. A descriptive Survey Research design was adopted for the study. Population of the study was 340 participants consisting of school administrators and teachers from 15 public schools in Cross Rivers State, Nigeria. A sample size of 169 participants was obtained using Research advisor (2006) while purposive and stratified random sampling techniques were used to draw the sample size of the study. A questionnaire titled “Relationship between Human Resource Management and Teacher Effectiveness Questionnaire “was used to obtain data for the study. Data collected was analyzed using frequency counts, mean and standard deviation while Pearson Product Moment Correlation Co-efficient was used to test the hypotheses generated at 0.5 level of significance. One of the findings from the study revealed that there was a strong positive relationship between training & development and teacher effectiveness in public secondary schools in Cross Rivers State, Nigeria. The study recommended among others that: The management should make adequate provision for teacher development opportunities to enable teachers update their skills and competence.